Nanoscale Organization of a Platinum(II) Acetylide Cholesteric Liquid Crystal Molecular Glass for Photonics Applications. (28th May 2020) - Cooper, Thomas M.; Haley, Joy E.; Stewart, David J.; Long, Stephanie; Krein, Douglas M.; Burke, Aaron R.; Arias, Eduardo; Moggio, Ivana; Turlakov, Gleb; Ziolo, Ronald F.; Biler, Michal; Linares, Mathieu; et al.
Abstract: The fabrication, molecular structure, and spectroscopy of a stable cholesteric liquid crystal platinum acetylide glass obtained from trans ‐Pt(PEt3 )2 (CC−C6 H5 −CN)(CC−C6 H5 −COO−Cholesterol), are described and designated as PE1‐CN‐Chol. Polarized optical microscopy, differential scanning calorimetry, and wide‐angle X‐ray scattering experiments show room temperature glassy/crystalline texture with crystal formation upon heating to 165 °C. Further heating results in conversion to cholesteric phase. Cooling to room temperature leads to the formation of a cholesteric liquid crystal glass. Scanning tunneling microscopy of a PE1‐CN‐Chol monolayer reveals self‐assembly at the solid−liquid interface with an array of two molecules arranged in pairs, oriented head‐to‐head through the CN groups, giving rise to a lamella arrangement. The lamella structure obtained from molecular dynamics calculations shows a clear phase separation between the conjugated platinum acetylide and the hydrophobic cholesterol moiety with the lamellae separation distance being 4.0 nm. Ultrafast transient absorption and flash photolysis spectra of the glass show intersystem crossing to the triplet state occurring within 100 ps following excitation. The triplet decay time of the film compared to aerated and deoxygenated solutions is consistent with oxygen quenching at the film surface but not within the film. The high chromophore concentration, high glass thermal stability, and long triplet lifetime in air show that these materials have potential as nonlinear absorbing materials. Abstract : A stable cholesteric liquid crystal platinum acetylide glass obtained from trans ‐Pt(PEt3 )2 (CC−C6 H5 −CN)(CC−C6 H5 −COO−Cholesterol) is prepared and characterized. The triplet state of the glass has a longer lifetime than that observed in solution. A monolayer of the compound shows a lamella arrangement with an array of two molecules arranged in pairs, oriented head‐to‐head through the CN groups.